MILITARY STANDOFF BETWEEN THE U.S. AND IRAN: THE PARTIES’ MILITARY POTENTIALS AND HYPOTHETICAL SCENARIOS OF CONFLICT DEVELOPMENT IN THE MIDDLE EAST - GANIEV, Takhir; KARYAKIN, Vladimir; ZADONSKY, Sergey (CENTRAL ASIA AND THE CAUCASUS, 2024)
The paper analyzes the physical and geographical conditions of the Iranian theater of operations, the combat capabilities of the Iranian armed forces and Iran’s military doctrine. It notes the growing combat potential of the Iranian Army, the Islamic Revolutionary Guard Corps and the Law Enforcement Force.The article provides an analysis of combat capabilities and the forecast of thelikely scenarios of U.S. and Israeli military operations against Iran. It assesses the parties’ probable losses in the military operation. It emphasizes the fact that, despite the overwhelming American military power, Iran’s armed forces can repel aggression using the “hybrid war” assets and methods and an asymmetric response to the enemy. There are also shortcomings in the work of the American expert community in analyzing and forecasting the development of the military and political situation around Iran, which can lead to grave consequences for the United States.